A study on the effect of emotional intelligence towards marketing effectiveness / Mohd Hadi Abidi - Abidi, Mohd Hadi (Faculty of Business and Management, 2015)
Due to globalization of the organization, emotional intelligence (EI) is something that needs to take seriously. Emotional intelligence (EI) will effect on the marketing effectiveness and performance of the each organizations. In the presence of Self- Awareness, Self-Management, Social Awareness and Relationship Management will lead to Emotional Intelligence (EI). This paper is to analyze the relationship among the effect of Emotional Intelligence (EI) towards Marketing Effectiveness. Data were obtained from 85 employees in any organization around Malacca. Pearson Correlation analysis has been carried out separately for each of these engagement variables to investigate the relationship towards them and Multiple Regression are done to find the most dominant domain in Emotional Intelligence (EI) that effect to Marketing Effectiveness. The finding indicates that all variables (Self-Awareness, Self-Management, Social Awareness and Relationship Management) have significant relationship towards Marketing Effectiveness and Self-Management becomes the most domains that affect Marketing Effectiveness.